Conceptual Framework of an Ideal Muslim Capital - Faiqa Khilat; Fariha Tariq (Journal of Islamic Thought and Civilization, 2019)
According to Islamic teaching the Muslim capital city should incorporate fundamental elements of socio- economic enrichment and also a hospitable glance for its visitors. Various cities in the history of Islamic world performed as administrative capitals such as Medina, Damascus, Kufa, Baghdad, Isfahan, Mash’had etc. Among these Baghdad was the first major purpose built capital city founded at the bank of river Tigris by the Muslims. It had a radial plan with social interactive spaces at its centre. In the modern times, we have the example of Islamabad which was also planned as the capital of Islamic Republic of Pakistan. The current research compares these two capital cities in order to discover the features which an Islamic world capital city should incorporate and depict. Furthermore, it will generate some general rules for planning capital city for the governing bodies of Islamic republics which would be helpful in futuristic facets.